Factors associated with pulmonary tuberculosis in elderly individuals: A protocol for a scoping review. - Francisco de Assis Moura Batista; Juliana Iscarlaty Freire de Araújo; Fernanda Cunha Soares; Thalyta Cristina Mansano Schlosser; Clarissa Terenzi Seixas; Thaiza Teixeira Xavier Nobre (PLoS ONE)
Background Tuberculosis (TB) is an infectious disease with a significant impact on public health, with the pulmonary form being the most critical. The disease poses numerous risks to the elderly population, as it often manifests concomitantly with other age-related illnesses, thereby complicating its diagnosis and management. Several causal and associated factors contribute to the disease. Objective The objective of this manuscript is to present a scoping review protocol aimed at mapping the available literature on factors associated with and contributing to the incidence of Pulmonary Tuberculosis (PTB) in the elderly. Methods and analysis The scoping review protocol was developed following the guidelines of the Joanna Briggs Institute (JBI) and the PRISMA-ScR checklist, and it has been registered on the Open Science Framework (DOI: 10.17605/OSF.IO/DHQVP). The databases to be searched include Medline via PubMed, Lilacs, Web of Science, Scopus, Embase, as well as gray literature through Google Scholar and the Brazilian Coordination for the Improvement of Higher Education Personnel (CAPES) Thesis and Dissertation Catalog. The search strategy is grounded on a research question formulated using the PCC acronym (P-Population; C-Concept; C-Context). Peer-reviewed journal articles, scientific books, editorials, conference proceedings, and theses/dissertations published in Portuguese, English, or Spanish between 2014 and 2024 will be included. Discussion Elderly individuals are more susceptible to diseases due to the natural decline in immune response to Mycobacterium tuberculosis, the causative agent of tuberculosis. In this age group, symptoms are often difficult to detect. Understanding the causal and associated factors of the disease contributes to favorable outcomes and helps reduce the transmission chain to the rest of the population.